2014
DOI: 10.1109/tlt.2014.2337900
|View full text |Cite
|
Sign up to set email alerts
|

Learning about Social Learning in MOOCs: From Statistical Analysis to Generative Model

Abstract: We study user behavior in the courses offered by a major Massive Online Open Course (MOOC) provider during the summer of 2013. Since social learning is a key element of scalable education in MOOCs and is done via online discussion forums, our main focus is in understanding forum activities. Two salient features of MOOC forum activities drive our research: 1. High decline rate: for all courses studied, the volume of discussions in the forum declines continuously throughout the duration of the course. 2. High-vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
114
1
8

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(127 citation statements)
references
References 22 publications
4
114
1
8
Order By: Relevance
“…Course tutors use forums to provide course information, generate discussion and support learners by answering questions. Brinton et al, observed that active tutor participation increased the discussion volume but did not slow down the decline in participation [9]. However, in other studies tutor participation did not prompt increase forum activity [10].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Course tutors use forums to provide course information, generate discussion and support learners by answering questions. Brinton et al, observed that active tutor participation increased the discussion volume but did not slow down the decline in participation [9]. However, in other studies tutor participation did not prompt increase forum activity [10].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Social learning is a key aspect of MOOCs platforms which supports scalable peer-based learning as well as acting as the main channel of interaction between teachers and students (Brinton et al, 2014) and between learners themselves. Sol, Beers, and Wals (2013) define social learning as "an interactive and dynamic process in a multi-actor setting where knowledge is exchanged and where actors learn by interaction and co-create new knowledge in on-going interaction" (p. 37).…”
mentioning
confidence: 99%
“…The use of both internal and external social networks in a MOOC is well appreciated by students (Castaño-Garrido, Maiz-Olazabalaga, & Garay-Ruiz, 2015), and their use is also very suitable for developing collaborative learning tasks (Brinton et al, 2014). On the other hand, sociograms and centrality measures are valuable tools for understanding the social network phenomena (Zhu, Watts, & Chen, 2010).…”
mentioning
confidence: 99%
“…Also there is the problem of information overload because, as MOOCs were launched for a large number of students worldwide, often the forums are overloaded. Thus, it becomes impossible for anyone to navigate the discussion to find significant information [19], [20]. Instructors also consistently report that teaching online is frustrating and higher levels of preparation time and contact time with individual students via email are major issues.…”
Section: International Journal Of Information and Education Technologmentioning
confidence: 99%